Kedudukan dan peranan banjar dalam sistem pemerintahan Desa di Kabupaten Tabanan - ADINAGARA, Pratama ([Yogyakarta] : Universitas Gadjah Mada, 2009)
The development of local autonomy at this time have been able to increase the independence and region’s physical development, these are supported by the region’s authorities distribution and sharing of profits. Most of the areas are trying to improve the creativity to be able to supply the area with planning design, implementation, and supervision of the implementation aspects of the development in the region. Democracy education also took place with a good progress which are could be seen by the community's role in the governance’s mechanism, but these things do not cover the weaknesses of the regional autonomy. This research is a normative-empirical research with descriptive tends, as it is intended to provide a detailed description of the local system of governance that applies at the local law communities in Bali which is reviewed with the qualitative method by using the basic theories of state law. The founding fathers has been trying to put large autonomy at the villages, this could be seen from the 1945 Constitution before amended, through the recognition of the local law communities which occupies most of the territory in Indonesia. When Act No. 5 Year 1975 and Act No. 5 Year 1979 prevailed, unities of local law community in the villages in Indonesia, take place as a part of the administrative region only that depend on the government to carry out day-to-day governance. Customary law of the community units in Bali can be the example, altho ugh many shortfalls that must be improved related to the duality of governance that took place in the village.